(untitled) (Bangladesh Veterinarian, 2025)
Trichosomoides crassicauda (T. crassicauda) is a nematode inhabiting the urinary bladder of wild and laboratory rats. Although often considered nonpathogenic, it can cause haemorrhagic cystitis, renal haemorrhages, and urinary calculi, thereby influencing interpretation of research findings. Here is the report of T. crassicauda infection in a laboratory rat colony in Bangladesh, emphasizing clinical features, diagnostic findings, and preventive measures. Infection was controlled through strict hygienic measures, along with treatment of infected and non-infected colonies using ivermectin, supplemented with iron, vitamin B complex, and zinc. Bang. vet. 2025. Vol. 42, No. 1 – 2, 38 – 43